Epizootiology of haemonchosis in dairy calves in the state of Rio de Janeiro, Brazil - Neto, Manoel Pimentel (Pesquisa Agropecuaria Brasileira, 2014)
By means of fecal examinations and necropsies the epizootiology of Haemonchus placei was studied during 2 years using 77 weaned hybrid calves (Zebu x Friesian) 6 to 12 months of age, under conditions existing in the country of Barra Mansa, State of Rio de Janeiro, Brazil. Relations between seasonal fluctuations and bioclimatographs were studied principally on the basis of mean monthly maximum temperatures (37°C) and mean monthly minimum temperatures (10°C), monthly rainfall, nutritional state of the animals, helminthic interaction, hypobiosis and spring rise of H. placei in animals naturally infected, not drenched with anthelmintics and maintained on natural pasture (Melinis minutiflora).